2021
DOI: 10.1097/mog.0000000000000792
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiota replacement to eradicate antimicrobial resistant bacteria in the intestinal tract – a systematic review

Abstract: Purpose of review Antimicrobial resistance is a rising threat to global health and is associated with increased mortality. Intestinal colonisation with multidrug-resistant organisms (MDRO) can precede invasive infection and facilitates spread within communities and hospitals. Novel decolonisation strategies, such as faecal microbiota transplantation (FMT), are being explored. The purpose of this review is to provide an update on how the field of FMT for MDRO decolonisation has developed during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…We also noted, alongside other studies 23,24,26 , a significant reduction in antimicrobial resistance genes (AMRs) (Table S5). Members of the Enterobacteriaceae Family dominated the pre-FMT environment and significantly decreased post-FMT, which gave way to members of the Lachnospiraceae Family, and an overall increase in bacterial diversity.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…We also noted, alongside other studies 23,24,26 , a significant reduction in antimicrobial resistance genes (AMRs) (Table S5). Members of the Enterobacteriaceae Family dominated the pre-FMT environment and significantly decreased post-FMT, which gave way to members of the Lachnospiraceae Family, and an overall increase in bacterial diversity.…”
Section: Discussionsupporting
confidence: 82%
“…To date, multiple studies have reported structural changes to the microbiota in rCDI after FMT 14,[22][23][24][25][26] . Specifically, they have observed an increase in the number of commensal bacteria 4 from the Phyla of Firmicutes and Bacteroidetes, and a decrease in Proteobacteria 27 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Faecal microbiota transplant (FMT) has been investigated to treat intestinal colonization with pathogens by reintroducing gut commensals into the intestine that are involved in both direct and indirect mechanisms of colonization resistance. For example, the success of FMT to treat C. difficile is associated with restoration of bile metabolism and SCFA production [100][101][102][103][104][105][106]. FMT has been used successfully to treat recurrent C. difficile infections with a higher success rate than antibiotic treatment [107].…”
Section: Harnessing Nutrient Competition To Restrict Intestinal Growt...mentioning
confidence: 99%
“…For example, the success of FMT to treat C. difficile is associated with restoration of bile metabolism and SCFA production [100–106]. FMT has been used successfully to treat recurrent C.…”
Section: Introductionmentioning
confidence: 99%